2013
DOI: 10.1017/s0266462313000263
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy for Diabetic Ulcers: Systematic Review and Meta-Analysis

Abstract: Due to the limited RCT evidence, it is not possible to conclusively establish the benefits and harms of treating diabetic lower limb ulcers with HBOT. No significant effects on amputation rates were found in the RCT evidence and in the high quality studies, no difference was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
3
37
0
1
Order By: Relevance
“…The benefit of hyperbaric oxygen therapy is even less clear. In a recent meta‐analysis of six randomized controlled trials and six observational studies, the observational studies showed a benefit, but the randomized trials did not, and none of the studies focused on older adults. A retrospective study also failed to show efficacy or effectiveness .…”
Section: Clinical Research On Chronic Woundsmentioning
confidence: 99%
“…The benefit of hyperbaric oxygen therapy is even less clear. In a recent meta‐analysis of six randomized controlled trials and six observational studies, the observational studies showed a benefit, but the randomized trials did not, and none of the studies focused on older adults. A retrospective study also failed to show efficacy or effectiveness .…”
Section: Clinical Research On Chronic Woundsmentioning
confidence: 99%
“…In addition, HBO is widely used as an adjunctive therapy for many conditions, such as diabetic ulcer healing, traumatic brain injury, and ischemic stroke. However, a recent meta-analysis of clinical trials for the latter three conditions found no conclusive evidence for benefit to the patient after HBO therapy (13,81,82).…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%
“…In addition, HBO is widely used as an adjunctive therapy for many conditions, such as diabetic ulcer healing, traumatic brain injury, and ischemic stroke. However, a recent meta-analysis of clinical trials for the latter three conditions found no conclusive evidence for benefit to the patient after HBO therapy (13,81,82).HBO treatment is relatively safe (83,84), and some studies have shown it has anti-inflammatory activity (85-87). These features support further research into HBO treatment as an adjunctive therapy candidate for a wide range of diseases (88).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ein Technology Assessment Report aus Kanada (O'Reilly et al 2013) analysierte 157 Arbeiten. Ein Technology Assessment Report aus Kanada (O'Reilly et al 2013) analysierte 157 Arbeiten.…”
Section: Hyperbare Sauerstofftherapieunclassified